Nietzsche and the «Disinterested Knowledge» of the Sophists - Carrión Caravedo, Úrsula (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
The aim of the present work is to approach the sophist tradition from a Nietzschean perspective. More specifically, we analyze how the sophists and the contest that develops between them serve the philosopher as a tool to confront the Platonic tradition. In order to do that, we first describe certain characteristics of the competition among sophists, which are compatible with the Nietzschean valuation of becoming. Secondly, we relate Nietzsche’s interpretation of homo mensura with his perspectivism and skepticism. Finally, we explain how the expression «culture of disinterested knowledge», referred to the sophists, aims to contrast them with the seriousness of the Platonic- Socratic tradition against which Nietzsche fights.
Keywords: relativism; perspectivism; contest; game; becoming